2020
DOI: 10.3389/fmicb.2020.592496
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Profiles and Molecular Mechanisms of Campylobacter From Chicken and Pig in China

Abstract: The purpose of this research was to characterize the antibiotic resistance profiles of Campylobacter spp. derived from chicken and pig feces collected from farms in Jiangsu Province, China, and to analyze the relevant resistance mechanisms among antimicrobial-resistant Campylobacter spp. isolates. Antibiotic susceptibility to nine antibiotic agents was tested with the microdilution method in 93 Campylobacter spp. (45 C. jejuni and 25 C. coli from chickens; 23 C. coli from pigs). High rates of resistance were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 58 publications
(92 reference statements)
8
34
2
Order By: Relevance
“…In regards to fluoroquinolones such as ciprofloxacin, we have determined a significant lower rate of resistance compared to 52.3% of the EFSA report [ 29 ]. Moreover, for erythromycin resistance, the low rates of resistance that we have recorded are in great difference with the data from China [ 30 ], where Tang et al found that all 23 (100%) C. coli isolates from pigs and overall 75.3% of Campylobacter isolates from poultry and pigs were resistant to erythromycin. These differences can be attributed to the fact that macrolides, including erythromycin, are the only antibiotics authorized by the Chinese government for use as feed additives [ 31 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In regards to fluoroquinolones such as ciprofloxacin, we have determined a significant lower rate of resistance compared to 52.3% of the EFSA report [ 29 ]. Moreover, for erythromycin resistance, the low rates of resistance that we have recorded are in great difference with the data from China [ 30 ], where Tang et al found that all 23 (100%) C. coli isolates from pigs and overall 75.3% of Campylobacter isolates from poultry and pigs were resistant to erythromycin. These differences can be attributed to the fact that macrolides, including erythromycin, are the only antibiotics authorized by the Chinese government for use as feed additives [ 31 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are similar to Woźniak-Biel et al (2016) [ 35 ] and El-Adawy et al (2012) [ 36 ], who revealed the same mutation in all ciprofloxacin-resistant Campylobacter strains from broilers and turkeys, respectively. Moreover, Tang et al [ 30 ] characterized the T86I amino acid substitution as the sole mutation recorded in quinolones resistant Campylobacter isolates from poultry and pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many reports showed that Campylobacter spp. from poultry and pig farms in China had high antibiotic resistance rates, particularly towards fluoroquinolones, tetracyclines and macrolides [ 41 , 42 , 43 ].…”
Section: Emergence Of Antibiotic-resistant Bacteria In Livestockmentioning
confidence: 99%
“…The use of antibiotics in poultry production is one of the major factors for the development of antibiotic resistance in C. jejuni (Sahin et al, 2002;Skarp et al, 2016). Antibiotic-resistant C. jejuni isolates have been observed and reported in recent years (Marotta et al, 2020;Tang et al, 2020;Hull et al, 2021). A recent study reported that some natural products, including plant extracts, essential oils, and pure phytochemicals, are effective against drug-sensitive and drug-resistant Campylobacter strains (Gahamanyi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%